2010
DOI: 10.1007/s10840-010-9490-8
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of atrial fibrillation after the retirement age: considerations on safety and outcome

Abstract: BACKGROUND: Although the incidence of atrial fibrillation (AF) progressively increases with age, the vast majority of AF ablation is done in middle-aged patients. We evaluated the feasibility and safety of catheter ablation in patients older than 65 years of age with paroxysmal and persistent AF. METHODS: Out of a total of 230 consecutive AF ablation procedures, 45 patients were older than 65 years of age and underwent 53 procedures. The ablation strategy consisted of wide-area circumferential lines around bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Recently, our group reported the clinical result of 45 consecutively enrolled patients aged 65 years or more with symptomatic paroxysmal and persistent AF undergoing catheter ablation for rhythm control [23]. Important structural heart disease was not documented in any of these elderly patients.…”
Section: Catheter Ablation Of Af In the Elderlymentioning
confidence: 99%
“…Recently, our group reported the clinical result of 45 consecutively enrolled patients aged 65 years or more with symptomatic paroxysmal and persistent AF undergoing catheter ablation for rhythm control [23]. Important structural heart disease was not documented in any of these elderly patients.…”
Section: Catheter Ablation Of Af In the Elderlymentioning
confidence: 99%
“…In a recently published study, we reported the clinical outcome of 45 consecutive patients over the age of 65 years who underwent a percutaneous catheter ablation procedure for symptomatic paroxysmal and persistent AF [57]. Among them, none had a significant structural heart disease.…”
Section: Catheter Ablation Of Af In the Elderlymentioning
confidence: 99%
“…10 Oral anticoagulants are highly effective in preventing AF-related stroke, but since the oldest patients are likely to have the highest risk for hemorrhage on warfarin, prescribing anticoagulation is a dilemma that clinicians face, especially for the geriatric population. [7][8] Another matter of contention is the issue of ratecontrol versus rhythm-control. The Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) trial pinned these treatment strategies against each other, only to find no significant difference in mortality.…”
Section: The Evidence For Pv Isolationmentioning
confidence: 99%
“…Reports assessing ablation for AF in the geriatric population have recently become available. [5][6][7][8] A brief overview of non-ablation invasive management strategies, including pacemakers, defibrillators, and the surgical maze procedure is then included.…”
Section: Introductionmentioning
confidence: 99%